Christians’ Prayer, Missio Dei, and Missio Ecclesiae: An Exegetical Study of 1 Timothy 2:1-7 - Pancha Wiguna Yahya (Universitas Pelita Harapan, 2020)
1 Timothy 2:1-15 is considered to be one of the most profound passages on prayer in the New Testament because it presents an extensive instruction on what and how Christians ought to pray. However, NT scholars are in dispute on the purpose of the instruction on prayer in this passage. It is common that this instruction, especially that of 2:1-7, is regarded as a general command for Christians to pray for all people and for government leaders. This article will demonstrate that in this passage, Paul exhorts the church in Ephesus to pray for all people, including kings, so that God’s mission to bring salvation to all mankind will be fulfilled. At the same time, Christians need to pray so that they may carry out their mission among the ungodly society by living godly and dignified lives in accordance with the apostolic teaching and resist the false teaching that permeates the church. The structure of the text will be examined grammatically to expound the meaning of this passage.